Pengaruh Penerapan Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2020)
This study aims to determine the effect of the application of accounting information systems on the quality of financial statements at PT. CSM Cargo. The research approach used in this research is descriptive analysis and causality using primary data. The sampling technique used is non-probability sampling using saturated samples. The statistical analysis used in this study is a simple linear regression analysis test, hypothesis testing using t test. The population of this research is the administration at PT. CSM Cargo. The research sample used was 47 people with data sources obtained through the results of filling out the questionnaire. Based on the results of research conducted can be seen that the application of accounting information systems affect the quality of financial statements. The results of this study indicate that the application of accounting information systems properly and correctly can improve the quality of financial statements.